The role of the military in the politics and government of Egypt during the Hosni Mubarak era and after him (Scientific Journal of Research Studies in Future Human Sciences, 2024)
The intervention of the army led to the revolution of 1952 and the overthrow of King Farouk, the king of this country, and the second time on the third day of July 2013, i.e. 61 years later, ended with the fall of the government of Mohamed Morsi.One of the most important political developments is the occurrence of popular uprisings in Arab countries. In the meantime, Egypt is considered as one of the most important countries in the Islamic world, which has been affected by Arab developments. With the formation of the 2011 revolution, the nation of this country had high hopes that the previous authoritarianism would pass to democracy. However, the existence of various causes and factors, including the role of the army in the political structure and government of this country, made the path of democracy in this country half-finished. The Egyptian army has changed the course of the country's political history twice.